A recyclable hydroxyl functionalized polyindole hydrogel for sodium hydroxide extraction via the synergistic effect of cation–π interactions and hydrogen bonding. Issue 70 (14th August 2018) - Chang, Guanjun; Wang, Yan; Wang, Cheng; Li, Yannan; Xu, Yewei; Yang, Li
Abstract : We have successfully constructed a new type of recyclable indole-based hydrogel, which exhibited highly effective extraction behavior for hydroxide via the synergistic effect of cation–π interactions and hydrogen bonds. Abstract : We have successfully constructed a new type of recyclable indole-based hydrogel, which exhibited highly effective extraction behavior for hydroxide via the synergistic effect of cation–π interactions and hydrogen bonds. More interestingly, the absorption performance could be visually detected by taking advantage of the color altering effect of the host–guest interactions.